2011
DOI: 10.1007/s12630-011-9593-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sitting up for five minutes versus immediately lying down after spinal anesthesia for Cesarean delivery on fluid and ephedrine requirement; a randomized trial

Abstract: Background Patient position after spinal anesthesia has had variable effects on blood pressure and ephedrine requirements. The aim of this study was to determine the effects that sitting the patient up for five minutes after spinal anesthesia would have on intraoperative fluid and ephedrine requirements. Methods The study included 120 women at term gestation who were scheduled for Cesarean delivery under spinal anesthesia. After anesthetic administration, the women were randomized either to sit up for five min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Except for the latter, none of these factors were altered in the current study, and hence, the observation that prolonged sitting progressively limited the sensory height of the subarachnoid block was attributed solely to the length of time spent in the sitting position. These findings are in keeping with those reported by others [6,10,11]. However, this is the first study that demonstrated that patients can set up for up to 7 min without compromising the success of the spinal anaesthetic.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Except for the latter, none of these factors were altered in the current study, and hence, the observation that prolonged sitting progressively limited the sensory height of the subarachnoid block was attributed solely to the length of time spent in the sitting position. These findings are in keeping with those reported by others [6,10,11]. However, this is the first study that demonstrated that patients can set up for up to 7 min without compromising the success of the spinal anaesthetic.…”
Section: Discussionsupporting
confidence: 92%
“…Several factors have been shown to affect the cephalad local anaesthetics when injected into the subarachnoid space including lumbosacral cerebrospinal fluid volume [9], local anaesthetic dose [3] and baricity [7], and patient position [3,6,10,11]. Except for the latter, none of these factors were altered in the current study, and hence, the observation that prolonged sitting progressively limited the sensory height of the subarachnoid block was attributed solely to the length of time spent in the sitting position.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The level of sensory block was significantly higher in group H compared to group L, which was accomplished with the use of the same dose of hyperbaric bupivacaine (12,5mg) in both groups. The difference in the level of sensory block was achieved by the tilt of the operating table with a slight anti-Trendelenburg position in group L. It was shown before that with the positioning of the patient, different levels of sensory block could be achieved (36)(37)(38). We decided for the dose of hyperbaric bupivacaine that is high enough to produce high spinal block (12,5mg), even in young patients.…”
Section: Discussionmentioning
confidence: 93%